Student Self-Declaration Forms: A Good Faith Approach to Academic Integrity - Morris, Heather; Stewart, Donald; Neville, Lukas; Harder, Nicole; Blair, Shinelle (Canadian Perspectives on Academic Integrity, 2023)
The University of Manitoba (U of M) recently approved a policy where students can submit a "Self-Declaration" Form in lieu of medical notes (and other documentation) when requesting academic arrangements for brief or temporary absences. The implementation of this policy demonstrates a shift to a new culture; trusting that students are responsible, and can act in good faith and with integrity when requesting assignment extensions or deferred exams. In this session, participants will hear from a panel representing the perspectives of administrators, faculty members, and students on the development, benefits, impact, and challenges encountered during the initial year of implementation of this policy.